Asuhan Keperawatan Jiwa pada Pasien dengan Gangguan Konsep Diri: Harga Diri Rendah di RSKD Dadi Provinsi Sulawesi Selatan Tahun 2024 - Nur Reski Anita; Sartika S; Nurhijrani N (Fatiakara Care: Jurnal Ilmiah Keperawatan, 2025)
Schizophrenia is a group of psychotic reactions that affect various areas of individual function, including thinking, communicating, feeling and expressing emotions, as well as brain disorders characterized by disorganized thoughts, delusions, hallucinations and strange behavior. Low self-esteem is one of the maladaptive responses in the range of neurobiological responses. Based on an initial survey on April 4 2024, data from RSKD Dadi South Sulawesi Province shows that the number of schizophrenia patients received in 2023 from June-December was 841, while in 2024 from January-February there were 1,092 patients. So the total number of data on schizophrenia patients throughout 2023-2024 is 1,933 people. Objective: To understand the description of the application of nursing care to patients with self-concept disorders: low self-esteem at the Dadi Regional Special Hospital, South Sulawasi Province. Method: Observation; mental status examination, which includes appearance, speech, feelings, interactions during the interview, thought content, level of consciousness, memory, level of concentration and numeracy. Results: After observing patients with low self-esteem disorders, the low self-esteem implementation strategy approach taught patients to interact in stages according to what the patient said. It is hoped that the research will be able to become a reference for further research in providing nursing care for patients with low self-esteem disorders.